Orientation of the Mitotic Spindle in Blood Vessel Development - Wu, Xuemei; Zhou, Jun; Li, Dengwen (Frontiers in Cell and Developmental Biology, 2020)
Angiogenesis requires coordinated endothelial cell specification, proliferation, and collective migration. The orientation of endothelial cell division is tightly regulated during the earliest stages of blood vessel formation in response to morphogenetic cues and the controlled orientation of the mitotic spindle. Consequently, oriented cell division is a vital mechanism in vessel morphogenesis, and defective spindle orientation can perturb the spatial arrangement of daughter cells and consequently contribute to several diseases related to vascular development. Many factors affect endothelial cell proliferation and orientation and therefore blood vessel formation, with the relationship between improper spindle orientation in endothelial cells and various diseases extensively studied. Here we review the molecular mechanisms driving the orientation of endothelial cell division, particularly with respect to the mitotic spindle, and how these processes affect vascular development, disease pathogenesis, and their potential as novel targets.